Essay on sejahtera: concept, principle and practice - Abdul Razak, Dzulkifli (IIUM Press, International Islamic University Malaysia, 2020)
The word sejahtera has its own place and meaning. Lest properly understood, the use can be baffling. For example, in the 2019 Budget, sejahtera was used to convey an aspect of socio-economic wellbeing of Malaysians, which in Malay reads as memastikan kesejahteraan rakyat. but fall short when confined only to "socio-economic" aspect. Sejahtera is a rather multilayered concept that conveys a deeper meaning than any single word can convey. As such it has no equivalent in other languages, neither can it be accurately translated into different languages due to its close cultural learning and nuances to the local Malay(sian) tradition.